Peran Lembaga Sosial dalam Mewujudkan Maqashid al-Syari’ah: Studi atas Peran Komisi Penanggulangan AIDS sebagai Upaya Hifz} al-Nafs dan PenanggulanganProstitusi Online - Nasrulloh . (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2016)
Online prostitution carried out for the sex trade. As with conventional prostitution, online prostitution aims to engage in intercourse with the payment. The impact of this is the emergence of prostitution sexually transmitted diseases (STDs), which can be deadly. Because this type of prostitution also lead to death, the law of Islam regulate everything that could eliminate the concept of the soul must be eliminated through hifz al-nafsi (maintaining the life). In legislation online prostitution is prohibited and the perpetrators get legal sanction. AIDS Commission (KPA) as the institution in charge of tackling HIV/AIDS in line with the goal of Islam in maintaining the life (hifzal-nafs). KPA must be enormous role as a social institution concerned in the field of HIV/AIDS is one of them arising from the impact of forced prostitution online.